1988
DOI: 10.1080/09291018809359963
|View full text |Cite
|
Sign up to set email alerts
|

The effects of feedback lighting on the circadian rhythm of locomotor activity and the reproductive maturation of the male Djungarian Hamster(Phodopus sungorus)

Abstract: The non-parametric model of entrainment suggests that brief pulses of light, delivered between dusk and dawn can simulate the phasing effects of full photoperiods or even constant light (LL). Feedback lighting (LDFB) is a lighting condition where individual animals, otherwise in constant darkness (DD), are exposed to light in response to a monitored behavior. The specific purpose of this type of illumination is to expose the circadian cycle to light only during the subjective night. LDFB has been used to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 57 publications
(63 reference statements)
1
1
0
Order By: Relevance
“…The circadian system of Siberian hamsters (Phodopus sungorus sungorus) has been characterized in detail by several laboratories. Circadian organization in this species is consistent with that of other nocturnal rodents with respect to parameters such as their photic PRC (Milette and Turek, 1986;Puchalski and Lynch, 1991a), conformity to Aschoff's rule (Ferraro, 1988;Puchalski and Lynch, 1991b), and behavior under various T-cycles (i.e., LD cycles different from 24 h) (Darrow and Goldman, 1985;Puchalski and Lynch, 1994). Recent studies have, however, revealed that unlike other nocturnal rodents, hamster circadian rhythms are prone to disruption by various light treatments.…”
supporting
confidence: 75%
“…The circadian system of Siberian hamsters (Phodopus sungorus sungorus) has been characterized in detail by several laboratories. Circadian organization in this species is consistent with that of other nocturnal rodents with respect to parameters such as their photic PRC (Milette and Turek, 1986;Puchalski and Lynch, 1991a), conformity to Aschoff's rule (Ferraro, 1988;Puchalski and Lynch, 1991b), and behavior under various T-cycles (i.e., LD cycles different from 24 h) (Darrow and Goldman, 1985;Puchalski and Lynch, 1994). Recent studies have, however, revealed that unlike other nocturnal rodents, hamster circadian rhythms are prone to disruption by various light treatments.…”
supporting
confidence: 75%
“…This also appears to be the case for Siberian hamsters that free-run, rather than become arrhythmic, after a 5-h phase delay of the LD cycle (25). These animals tend to free-run with a mean rhythm period that is no different from hamsters housed in LL (7,8,19). Although these phenomena suggest that the behavior of unentrained free-running or arrhythmic hamsters bears some similarity to animals held in LL, their failure to regain rhythms in DD does not.…”
Section: Discussionmentioning
confidence: 78%